Does behaviour matters the most in improving urban immunization coverage: exploring behavioural barriers in northern states of India - Pritu Dhalaria; Ayushi Agrawal; Jaideep Kumar; Ajeet Kumar Singh; Ashish Maurya; Syed Hassan; Bhupendra Tripathi; Arindam Ray; Sanjay Kapur (Vaccine: X)
Background: Immunization is a crucial public health achievement, yet achieving equitable coverage remains challenging in countries like India. Despite India's notable progress in its Universal Immunization Program (UIP), urban-rural discrepancies persist, especially in densely populated states like Bihar and Uttar Pradesh, with urban areas experiencing slower improvement in coverage. Data & methodology: This study, conducted in Bihar and Uttar Pradesh, aimed to explore behavioural and social determinants affecting immunization uptake in urban areas. Based on the WHO's Behavioural and Social Drivers of Vaccination (BeSD) model, a comprehensive baseline situation analysis, including 34 in-depth interviews and 27 focus group discussions, was conducted in 12 districts of Bihar and Uttar Pradesh. The assessment covered the perceptions of caregivers, healthcare providers, and key immunization stakeholders. Results: Findings are categorized within the BeSD model's four domains: Thinking and Feeling, Social Processes, Motivation, and Practical Issues. In the thinking and feeling domain, perceived understanding gaps, the need for awareness, and the role of mass media and social networks emerged as key themes. Social processes illuminate gender dynamics, the dominance of decision-making by male and elderly members, and the impact of domestic violence on vaccination choices. Motivational factors include concerns about vaccine quality, fear of adverse events, and the influence of religious leaders. Practical issues encompass distrust of healthcare personnel, the timing of vaccination sessions, and infrastructural. Conclusion: The study reveals multifaceted challenges, highlighting the need for targeted urban-specific strategies to address social and behavioural barriers, enhance awareness, and improve infrastructure in urban immunization programs.